Too big to fail : policies and practices in government bailouts - Gup, Benton E. (Praeger, 2004)
Usually associated with large bank failures, the phrase too big to fail, which is a particular form of government bailout, actually applies to a wide range of industries, as this volume makes clear. Examples range from Chrysler to Lockheed Aircraft and from New York City to Penn Central Railroad. Generally speaking, when a corporation, an organization, or an industry sector is considered by the government to be too important to the overall health of the economy, it will not be allowed to fail. Government bailouts are not new, nor are they limited to the United States. This book presents the vi.